P170 Long-term effectiveness of omalizumab in patients with severe persistent allergic (IgE-mediated) asthma: UK centre real-life experience. (14th November 2013) - Mansur, AH; Mitchell, V; Alfridi, L; Sullivan, J; Kasujee, I
Abstract : Omalizumab has been shown to be an effective add-on therapy for patients with uncontrolled severe persistent allergic (IgE-mediated) asthma. There has been a steady accumulation of evidence on long-term effectiveness of omalizumab; however, data on real-life outcomes beyond one year of treatment in a UK clinical setting is limited. In this analysis, data were compared for a number of patients from the Heartlands Hospital (Birmingham, UK), to determine if improvements were sustained with longer-term treatment. Patients (n = 45, mean age 44.9 years, range: 19–69) received omalizumab for a mean duration of 49.3 months (range: 23–96). All patients with available data (n = 18/45) showed a clinically relevant improvement in asthma control questionnaire (ACQ) scores post-omalizumab (mean ?ACQ: 2.27, range: 0.5–4.1; mean baseline ACQ: 4.1, range: 3.7–4.7). In patients on oral corticosteroids (OCS) vs patients not on OCS (at baseline), improvements were greater: ACQ of patients on OCS at baseline was 4.1 and 1.6 post treatment vs 4.0 at baseline and 2.7 post treatment. Mean OCS dose reduced pre- to post-omalizumab: 30.5 to 7 mg/day. Reductions in hospital admissions/bed days were seen post-treatment (figure). There were also reductions in work/school days missed in 17/19 patients; the other 2 patients showing no change. Overall mean FEV1 was improved in the majority of patients with available data (17/20). Results from this real-life follow-up study demonstrate that improved outcomes in patients with severe allergic asthma are sustained with longer-term omalizumab therapy.